2017
DOI: 10.1111/1346-8138.14156
|View full text |Cite
|
Sign up to set email alerts
|

Early cutaneous eruptions after oral hydroxychloroquine in a lupus erythematosus patient: A case report and review of the published work

Abstract: Hydroxychloroquine (HCQ) is an effective treatment of lupus erythematosus. Although adverse effects, mainly gastrointestinal and cutaneous manifestations, are rare, they may result in the cessation of medication in some patients with severe reactions. Therefore, the evaluation of a patient's condition is important for a dermatologist to decide whether to cease or continue HCQ. We herein report a case of a 36-year-old Japanese woman with systemic lupus erythematosus and cutaneous eruptions caused by the p.o. ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 8 publications
2
22
0
2
Order By: Relevance
“…6 Among our patients with AE, six patients could be re-administrated HCQ without the recurrence of AE. Similar to our cases, Matsuda et al 7 also reported that withdrawal of HCQ was not…”
supporting
confidence: 91%
“…6 Among our patients with AE, six patients could be re-administrated HCQ without the recurrence of AE. Similar to our cases, Matsuda et al 7 also reported that withdrawal of HCQ was not…”
supporting
confidence: 91%
“…There were two patients with skin eruptions; however, one patient (with maculopapular type) restarted HCQ without further adverse events. Matsuda et al . reported that they continued HCQ therapy in a patient who developed a mild skin eruption, and her skin symptoms disappeared within 1 week under continuous HCQ treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The ma jor i ty of the data comprise skin disorder and gas troin testinal disorders such as diarrhea, and there are 2 cases of urticaria. It is sometimes difficult to establish whether early cutaneous eruptions that appear after the initiation of oral HCQ are due to HCQ or a flare of disease [6] .…”
Section: Discussionmentioning
confidence: 99%